What Drives Design Education in Korean Classrooms? The History of South Korea's National Curriculum and Some Proposals for Design Education in Its Current Iteration - Choi, Seolyung; Hyun, Eunryung (The international journal of art & design education, 2025)
In South Korea, the National Curriculum and textbooks, especially within design education, are closely intertwined. The Curriculum is critical in establishing educational goals and standards for each subject, acting as a blueprint for schooling. Textbooks, which must be approved, are designed to align with this Curriculum. This article introduces new content for design textbooks guided by the 2022 Curriculum revisions, highlighting the importance of using design to solve real‐world problems and the potential for interdisciplinary collaboration. Consequently, this article puts forth the following proposed content to be included in the forthcoming design textbook: recognising and appreciating exemplary design in everyday life, acquiring diverse knowledge to foster creative problem‐solving skills, and comprehending the significance of design for all individuals.